Talent management practices for minimising talent turnover in a public sector organisation - Edith E. Gandi; Musawenkosi D. Saurombe (South African Journal of Economic and Management Sciences, 2025)
Background: Public sector organisations often invest in the employment of skilled or promising public officials. However, there is an ongoing trend of public sector employees using their government employment as a stepping stone to greener pastures, as these organisations are often unable to effectively manage and ultimately retain their human capital.